PERSEPSI PETANI TERHADAP KARAKTERISTIK PRODUK BARU DALAM KEPUTUSAN ADOPSI NASABAH PEMBIAYAAN SYARIAH - Henny Indrawati (Fakultas Pertanian, Universitas Riau, 2011)
This study aims to determine the farmer's perception of sharia finance products. Theresearch method used is descriptive qualitative. The unit of analysis is the study of oilpalm farmers in Kampar regency which become customers of products murabahafinancing of oil palm plantations Riau Sharia Bank Branch Pekanbaru. Study samplewas determined by using Random Sampling Proportional to account for 50 farmers. Theresearch was conducted from January to April 2011. The results showed the newproduct adoption decisions (murabaha financing products of oil palm plantations) isinfluenced by five characteristics perceived by farmers as customers, namely relativeadvantage, suitability (compatibility), complexity, it is likely to be tried first (triability),and ease communicated (communicability). The more superior product murabahafinancing of oil palm plantations Riau ShariaBank compared with existing products(loans from conventional banks or financing from other sharia banks), the greater theadoption decisions of farmers. The higher the conformity of products murabahafinancing of oil palm plantations Riau Sharia Bank, the more likely farmers' adoptiondecisions. Increasingly difficult financing products of oil palm plantations murabahaRiau Sharia Bank understand and use, the lower the likelihood of adoption decisions offarmers. The easier the financing products of oil palm plantations murabaha Riau ShariaBank to try and communicate, the more likely farmers' adoption decisions.Key words: perception, new product characteristic, adoption decision